Geotechnical Stability Analysis of the Quay Wall of Port Ksar Sghir, Morocco - Ait Boujmaa, Mohamed; Khelalfa, Houssam (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2022)
This article consists in establishing a geotechnical stability study of the -4m/zh quay belonging to the Ksar Sghir Port. First of all, using the TALREN software for verification against large slips. the study presents a verification of the stability for the rear slope slip circles and for the front slope slip circles in the static case. Secondly, stability was determined for the back slope slip circles and for the front slope slip circles in the seismic case. Moreover, PLAXIS software was used to model the displacements and constraints in the structure. Following the results of the safety coefficients, we notice that the stability of the structure gives acceptable values. In addition, the soil does not reach breaking stress. The total mean stress and total displacement mostly impacted the surface area that is related to external impact.